Nurturing Religious Moderation through Pesantren Traditions: A Case from the Bangka Belitung Islands - Rudini; Subri (Al-Ulum, 2024)
This article examines the values of religious moderation within the tradition of Islamic boarding schools (pesantren), which are renowned for consistently embodying the four key indicators of religious moderation. This research-based paper departs from facts in the field using qualitative research analysis with a qualitative descriptive design. Data collection techniques are sourced from observation, interviews, and document review. These values are reflected in daily life, education systems, and teaching practices. Several factors influence the strong connection between moderation and pesantren traditions: (1) the close-knit relationships among community members—leaders, religious teachers, and students—who live together under one roof; (2) the students' obedience to their kyai and teachers, reflecting deep respect and belief in spiritual blessings; (3) a modest lifestyle characterized by simplicity, frugality, carefulness, and communal living; (4) the cultivation of independence in fulfilling duties, responsibilities, and daily needs; (5) a strong sense of togetherness, mutual assistance, and brotherhood.